Energy content analysis of extruded briquettes: effects of mesh granularity and corn cob-to-coconut shell residue blend composition - Khamdi Mubarok; Teguh Prasetyo; Ian Budi Pratama (Jurnal Polimesin, 2026)
The conversion of agricultural residues into biomass briquettes presents a sustainable alternative for energy generation, addressing waste management challenges, reducing fossil fuel dependence, and mitigating carbon emissions. This study analyzes the influence of material mesh granularity and corn cob-to-coconut shell residue blend composition on the energy content and quality metrics of extruded briquettes. The primary objective is to investigate the effects of formulation parameters on energy yield (calorific value), structural durability (shatter index), and ash content. Employing an experimental approach combined with statistical analysis (Analysis of Variance (ANOVA) and Friedman test), the impacts of varying mesh sizes and compositional mass ratios were systematically evaluated. The results showed that calorific values ranged between 4,739–5,143 cal/g, ash content varied from 14.95–23.62%, and the shatter index from 0.04–1.33%. The optimal performance was obtained at 50 mesh with 70% corn cob charcoal and 30% coconut shell residue, yielding the highest calorific value (5,143 cal/g), the lowest ash content (16.66%), and excellent durability (shatter index 0.04%). Statistical analysis (ANOVA and Friedman test) confirmed that both particle size and blending ratio significantly affected all quality metrics (p 0.05). These findings provide actionable insights for enhancing energy content and overall quality of extrusion-derived briquettes from agricultural residues. The research underscores the essential role of precise material selection and parameter control in developing efficient and sustainable solid biomass fuels.